Multi-party summation query method based on differential privacy - Xianmang HE (网络与信息安全学报)
Differential privacy is considered to be a very reliable protection mechanism because it does not require the a prior knowledge for the attacker.However,differential privacy is rarely used in a multi-party environment.In view of this,the differential privacy is applied to the data summation query in multi-party environment.This method was described in detail and proved the security of the method.